Circulating Angiogenic Factors in Patients with Thromboangiitis Obliterans - Hewing, Bernd; Stangl, Verena; Stangl, Karl; Enke-Melzer, Kathrin; Baumann, Gert; Ludwig, Antje (PLOS ONE, 2012)
Background Thromboangiitis obliterans (TAO, also known as Buerger's disease) is a non-atherosclerotic inflammatory vascular disease that primarily affects arteries in the extremities of young adult smokers. Since the etiology of TAO is still unknown, therapeutic options are limited. Recent attempts in therapeutic angiogenesis have been promising. Therefore, the aim of our study was to evaluate angiogenic processes and factors including circulating progenitor cells in TAO. Methodology/Principal Findings TAO patients with critical limb ischemia and age- and gender-matched nonsmokers and smokers without cardiovascular disease (n = 12 in each group) were enrolled in the study. Flow cytometric analysis of peripheral blood showed significantly decreased levels of circulating CD45dimCD34+ progenitor cells in TAO patients and in smokers compared to nonsmokers. In contrast to both control groups, the proportion of CD45dimCD34+ progenitor cells co-expressing VEGF receptor-2 (VEGFR2) was significantly elevated in TAO patients. Enzyme-linked immunosorbent assay (ELISA) of common angiogenic factors (such as VEGF) did not clearly point to pro- or antiangiogenic conditions in serum or plasma of TAO patients. Serum of TAO patients and controls was evaluated in proliferation, migration (scratch assay) and spheroid sprouting assays using human umbilical vein endothelial cells (HUVECs). Serum of TAO patients exhibited a diminished sprouting capacity of HUVECs compared to both control groups. Proliferation and migration of endothelial cells were impaired after treatment with serum of TAO patients. Conclusion Levels of circulating progenitor cells were altered in TAO patients compared to healthy nonsmokers and smokers. Furthermore, serum of TAO patients exhibited an antiangiogenic activity (impaired endothelial cell sprouting, migration and proliferation) on endothelial cells, which may contribute to vascular pathology in this patient population.